QUALITATIVE ANALYSIS OF PUBLIC UNDERSTANDING OF FINANCIAL TECHNOLOGY (FINTECH)-BASED INVESTMENT RISKS IN TEMBILAHAN - Risma Tia Meilinda; Lili Suryani; Syafrinadina (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2025)
This study aims to analyze and describe in depth the understanding of the Tembilahan community regarding the risks associated with Financial Technology (Fintech)-based investments. The research method used is qualitative with a descriptive approach, focusing on data collection through in-depth interviews and observations of individuals who serve as research samples. The analysis focuses on the level of public awareness of various types of online investment risks (such as fraud, market volatility, and personal data security), the information sources they use, and the factors that influence their investment decision-making. The results of this study are expected to provide a comprehensive picture of digital financial literacy among the local community and provide valuable input for regulators and Fintech service providers in designing more effective education strategies to improve consumer protection and foster a safer and more informed investment ecosystem.